2017 23rd International Conference on Automation and Computing (ICAC) 2017
DOI: 10.23919/iconac.2017.8082034
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for transmission power control protocols in wireless sensor networks

Abstract: Abstract-This study investigates the opportunities for transmission power control (TPC) protocols in resource constrained wireless sensor networks (WSNs). The paper begins by creating a generalised model to describe the relationship between transmission power, communication reliability and energy consumption. Applying this model to the performance of state-of-the-art radio hardware, the maximum potential energy savings achievable through the implementation of a TPC protocol are identified. From this, previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Authors in [2] give explanations to quantify the energy dissipated by the transmitting and receiving antennas and they describe the Heinselman-Chandrakasan-Balakrishnan (HCB) energy model [3]. Moreover, the authors of paper [2] give metrics of the power drain properties of state-of-the art radio antenna design. In our research, a Wi-fi Radio Energy Model was used that defines 4 states TX, RX, IDLE and SLEEP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors in [2] give explanations to quantify the energy dissipated by the transmitting and receiving antennas and they describe the Heinselman-Chandrakasan-Balakrishnan (HCB) energy model [3]. Moreover, the authors of paper [2] give metrics of the power drain properties of state-of-the art radio antenna design. In our research, a Wi-fi Radio Energy Model was used that defines 4 states TX, RX, IDLE and SLEEP.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the different reasons for saving energy, it agrees with all research reviewed that saving energy is of great importance. Different approaches have been made to tackling this area of research, for example in [1] an empirical model was used, in [2] authors focused more on the characteristics of antennas and power consumption. In [6] authors were interested with determining the link quality and number of bits to transmit to determine the transmission power.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works have shown that TPC protocols are able to achieve significant energy savings. As quantified in "unpublished" [6], modulating the TP can reduce the energy consumed by communication activities by up to 80% for links that exist in the connected region and 66% for links that exist in the disconnected region. On top of this, previous works have reported improvements to spectrum efficiency and packet delivery as a result of interference suppression and minimising the bit error rate through ensuring sufficient link budget.…”
Section: Introductionmentioning
confidence: 99%
“…TPC is the intelligent selection of transmission output power in a wireless communication system and has been shown in several research works to significantly reduce the energy consumption of wireless communication activities. For example, energy savings of up to 80% were reported in [5]. Through the implementation of a TPC protocol, communication can be carried out at the minimum energy cost, i.e.…”
Section: Introductionmentioning
confidence: 99%